2018
DOI: 10.1086/694933
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Sprint Swimming Performance of Juvenile Striped Bass,Morone saxatilis

Abstract: Annual hypoxia in the Chesapeake Bay has expanded to the point where Darwinian fitness of juvenile striped bass (Morone saxatilis) may depend on their ability to perform in low-oxygen environments. The locomotion they use in predator/prey dynamics relies primarily on white (type II) muscle that is powered by anaerobic metabolic pathways and has generally been thought to be immune to aquatic hypoxia. We tested the sprint performance of 15 juvenile striped bass twice under acute hypoxia (20% air saturation [AS])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Our results further support the use of sprint speed as proxy for individual performance capacity in this lizard species, as has been established in some fish species (e.g., Oufiero and Garland 2009). To our knowledge, this is the first study to establish the repeatability of sprint speed under hypoxic con- ditions in lizards, corroborating a recent study in striped bass (Morone saxatilis) that found individual consistency in swimming speed under hypoxic conditions (Kraskura and Nelson 2018). As we predicted based on previous work in a variety of taxa, lizards adjusted blood chemistry in response to high-altitude hypoxia (Storz 2007;Storz et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Our results further support the use of sprint speed as proxy for individual performance capacity in this lizard species, as has been established in some fish species (e.g., Oufiero and Garland 2009). To our knowledge, this is the first study to establish the repeatability of sprint speed under hypoxic con- ditions in lizards, corroborating a recent study in striped bass (Morone saxatilis) that found individual consistency in swimming speed under hypoxic conditions (Kraskura and Nelson 2018). As we predicted based on previous work in a variety of taxa, lizards adjusted blood chemistry in response to high-altitude hypoxia (Storz 2007;Storz et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Under hypoxic conditions that restrict aerobic metabolism, fish may be forced to prioritize specific oxygen-consuming physiological processes. Voluntary swimming activity, for instance, may be limited under hypoxia (Schurmann and Steffensen, 1994; Kraskura and Nelson, 2018), as aerobic scope will be reduced (Richards, 2009). Importantly, reductions in swimming capacity with increasing hypoxia have been shown in several fish species of commercial importance, including cod Gadus morhua (Schurmann and Steffensen, 1994), dogfish Scyliorhinus canicula (Metcalfe and Butler, 1984) and sole Solea solea (Dalla Via et al , 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that fishing can occur in hypoxic areas is perhaps best reflected by the reported surges in capture where fishing and low oxygen co-occur (Gray, 1992; Breitburg, 2002). A possible explanation for this increase in catch is the constraining effect of hypoxia on fish locomotor or sensory physiology (Kraskura and Nelson, 2018), which may inhibit escape responses. Given that active fishing gears (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, for active, pelagic fishes like striped bass, performance under hypoxia tolerance may be a more relevant metric (e.g. Kraskura and Nelson, 2018). HT also appears to be a highly plastic and contextdependent physiological trait in fishes and it varies substantially among individuals of the same size, age and species (Nelson et al, 2019;Nelson and Lipkey, 2015;Killen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%